Systemic sclerosis - review of current data and latest reports - Radosław Kasperski; Tomasz Łoś; Anna Sobstyl; Dominik Dudziński; Małgorzata Piekarska-Kasperska (Kazimierz Wielki University, 2023)
Introduction: Systemic scleroderma (SSc) is an autoimmune disease characterized by fibrosis of the skin and internal organs, vasculopathy and dysregulation of the immune system. It has the highest mortality rate among rheumatologic diseases. SSc causes high economic and social costs. Aim of the study: The purpose of this review is to present the current state of knowledge and recent reports on the pathophysiology, clinical manifestation and treatment of SSc. Materials and methods: A search was conducted using PubMed and GoogleScholar databases. Articles were searched in English using the following keywords: "systemic sclerosis", "scleroderma", "treatment", "symptoms", "pathophysiology". Conclusions: Although the prognosis of SSc remains poor, optimized patient diagnosis along with ongoing advances in therapy could significantly impact the effectiveness of disease management in the near future. It is anticipated that there will be a growing need for further development of combination therapies to better treat this complex disease.